Perspectives of immunotherapy in isocitrate dehydrogenase-mutant gliomas - Friedrich, Mirco; Bunse, Lukas; Wick, Wolfgang; Platten, Michael (Current opinion in oncology, 2018)
Purpose of review The present review introduces recent progress in eliciting the role of mutant isocitrate dehydrogenase (IDH) in gliomas, especially regarding its mode of action as a modulator of antitumor immune response, and provides rationales for targeting mutant IDH in glioma immunotherapy. Both the development of small molecule inhibitors repressing the enzymatic activity of mutant IDH and novel, mechanism-led combination immunotherapies are discussed. - Recent findings Since the discovery of highly frequent IDH mutations in low-grade gliomas and nonsolid malignancies, its tumor cell-intrinsic effects have been intensively investigated. Tumor cells expressing mutant IDH display profound alterations of redox control capacity, phospholipid profile, and ATP supply. Recent findings suggest that IDH mutations - via intricate, yet druggable pathways - cause immunological alterations, highlighting the importance of oncogenic drivers as modulators of antitumor immunity and targets for immunotherapy. - Summary Mutant IDH is not only a disease-defining biomarker and oncogenic driver in glioma, but is also a neoantigen and a regulator of glioma immune evasion. Effective and specific strategies targeting the immunomodulatory properties of mutant IDH may complement current (immuno-)therapeutic strategies and approved antiglioma treatments to improve outcome.
Gesehen am 25.07.2019
Doi funktioniert nicht